The HUBUNGAN BERMAIN GAME ONLINE DENGAN KESEHATAN MENTAL SISWA SMK - Widodo, Yessy Pramita; Hidayat, Firman; Khaerunnisa, Nabila (Jurnal Keperawatan Malang, 2025)
Background: Internet users have made technological development easier and can be accessed from anywhere. Internet users use it for entertainment such as playing online games. Playing online games with high intensity can disrupt health and have a negative impact on mental health. Purpose: The general objective of this study was to determine the relationship between playing online games and the mental health of students at SMK Peristek Pangkah. Methods: This study used a descriptive correlation design, with a cross sectional approach. The population in this study were grade X students and grade XI students who played violent online games with warfare themes with sampling techniques using total sampling with a total of 100 respondents. Data analysis using Pearson Product Moment with Kendalls Tau-b. Result: The results of the data analysis obtained a P value = 0.001 <0.005, it can be concluded that there is a relationship between playing online games and the mental health of students at SMK Peristek Pangkah. Implication: students give time limits in online gaming by arranging a schedule of activities every day to prevent mental health disorders. Students are encouraged to do more positive activities such as joining organizations or extracurricular activities at school or activities that are liked and more useful so as not to cause mental health problems. Keywords: Playing Online Games; Mental Health